Does Valproic Acid Induce Neuroendocrine Differentiation in Prostate Cancer?. (25th October 2010) - Sidana, Abhinav; Wang, Muwen; Chowdhury, Wasim H.; Toubaji, Antoun; Shabbeer, Shabana; Netto, George; Carducci, Michael; Lupold, Shawn E.; Rodriguez, Ronald
Abstract : Valproic Acid (VPA) is a histone deacetylase inhibitor that holds promise for cancer therapy. Here, we investigate whether VPA treatment induces neuroendocrine differentiation of Prostate Cancer (PCa). A tissue microarray of VPA-treated and untreated tumor xenografts and cell lines of human PCa (LNCaP, C4-2, DU145, and PC-3) were generated and were analyzed by immunohistochemical analysis (IHC) for NE markers chromogranin A (CgA), synaptophysin, and NCAM (neural cell adhesion molecule). Western blot analysis for CgA was performed to confirm the results of the TMA. IHC analysis did not reveal any induction of CgA, synaptophysin, or NCAM in any xenograft after VPA treatment in vivo . In vitro, VPA treatment induced little synaptophysin expression in C4-2 and PC-3 cells and NCAM expression in LNCaP and PC-3 cells. In the case of CgA, VPA treatment decreased its expression in vitro in a dose-dependent manner, as determined by western blot analysis. Thus our data demonstrates that VPA does not induce NE differentiation of PCa cells in the physiologically relevant in vivo setting.